Detecting Unauthorized Access Points in Wireless Environment - Meenakshi, S.P; Thomas, Jacintha; Balaji, K S; Narayanan, Sathya N; Raman, Shankar; Kamakoti, V (International Journal of Computer Sciences and Engineering, 2025)
The exponential growth in wireless environment ensures extended mobility to the end-users. Mobility provides different levels of flexibity in operation but induces certain security risks. The security risks exist mainly in the form of unauthorized or fake access points to which end users can connect. The illegitimate connections could lead to eavesdropping on the end users and initiating security attacks (such as evil twins exploit). In this paper, we propose a method which uses label-hopping technique to detect fake wireless Access Point (AP). Once detected, such fake AP could be identified and removed from the wireless environment. We use Wireless Local Area Network (WLAN) based environment, as an example for applying the proposed technique. The proposed technique is extensible to mobile wireless networks such as 4th=5th generation mobile